Synthesis and formation mechanism of all-organic block copolymer-directed templating of laser-induced crystalline silicon nanostructures - Tan, Kwan Wee (2020)
This report describes the generation of three-dimensional (3D) crystalline silicon continuous network nanostructures by coupling all-organic block copolymer self-assembly-directed resin templates with low-temperature silicon chemical vapor deposition and pulsed excimer laser annealing. Organic 3D mesoporous continuous-network resin templates were synthesized from the all-organic self-assembly of an ABC triblock terpolymer and resorcinol–formaldehyde resols. Nanosecond pulsed excimer laser irradiation induced the transient melt transformation of amorphous silicon precursors backfilled in the organic template into complementary 3D mesoporous crystalline silicon nanostructures with high pattern fidelity. Mechanistic studies on laser-induced crystalline silicon nanostructure formation revealed that the resin template was carbonized during transient laser-induced heating on the milli- to nanosecond timescales, thereby imparting enhanced thermal and structural stability to support the silicon melt–crystallization process at temperatures above 1250 °C. Photoablation of the resin material under pulsed excimer laser irradiation was mitigated by depositing an amorphous silicon overlayer on the resin template. This approach represents a potential pathway from organic block copolymer self-assembly to alternative functional hard materials with well-ordered 3D morphologies for potential hybrid photovoltaics, photonic, and energy storage applications.